Adalimumab in Japanese patients with active ulcers of pyoderma gangrenosum: Twenty‐six‐week phase 3 open‐label study. Issue 12 (17th August 2020) - Yamasaki, Kenshi; Yamanaka, Keiichi; Zhao, Yiwei; Iwano, Shunsuke; Takei, Keiko; Suzuki, Koji; Yamamoto, Toshiyuki
Abstract: This phase 3 multicenter study, including 26‐week treatment and extension periods, evaluated the efficacy and safety of adalimumab in Japanese patients with active ulcers due to pyoderma gangrenosum. Patients received adalimumab 160 mg at week 0, 80 mg at week 2, and then 40 mg every week starting at week 4. Of the 22 enrolled patients, 12 (54.5%, P < 0.001) achieved the primary efficacy end‐point of pyoderma gangrenosum area reduction 100 (PGAR 100, defined as complete skin re‐epithelialization) for the target ulcer at week 26 assessed by digital planimetry. PGAR 100 response was observed as early as week 6 (13.6%) and continued to increase over time. The mean percent change from baseline in target ulcer area was −31.8% at week 6 and −63.8% at week 26. A Physician's Global Assessment score of 0 (PGA 0, all ulcers completely clear) was achieved by two patients (9.1%) at week 6 and eight (36.4%) at week 26, while PGA 0/1 (completely/almost clear) was achieved by five (22.7%) and 12 patients (54.5%) at week 6 and 26, respectively. Mean changes from baseline in pain numeric rating scale (−1.8 at week 6 and −2.5 at week 26) and the Dermatology Life Quality Index (−3.1 at week 6 and −3.6 at week 26) improved over time. Adverse events were reported by 18 patients, most commonly infections ( n = 11), and serious adverse events by four. These results suggest that adalimumab is effective and generally well tolerated in Japanese patients with active ulcers of pyoderma gangrenosum.